2011
DOI: 10.1111/j.1748-7692.2010.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Call sharing across vocal clans of killer whales: Evidence for vocal imitation?

Abstract: In killer whales or orcas (Orcinus orca) vocal matching appears to be an important aspect of within-group communication, but fish-eating “resident” orcas frequently associate with whales that share little or none of their repertoire. The production of calls belonging to another group's repertoire would allow vocal matching in such contexts and has been observed in captive and free-living orcas. However, reports were largely descriptive and neither structure nor usage of such “resemblance calls” have been inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…Playback experiments with groups of killer whales off Kamchatka found that the whales matched calls of pod members but not calls from different pods (Filatova et al, 2011). It is possible the killer whales are also capable of matching calls at the level of regional clans (Weiß et al, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…Playback experiments with groups of killer whales off Kamchatka found that the whales matched calls of pod members but not calls from different pods (Filatova et al, 2011). It is possible the killer whales are also capable of matching calls at the level of regional clans (Weiß et al, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…J. O. Miller, Shapiro, Tyack, & Solow, 2004). Much of the interest in orca vocalizations comes not from any particularly unusual features of their calls or their usage, but from the fact that stable social groups of orcas use a shared repertoire of sounds that is so consistent that recordings of particular sounds can be used to identify particular families of orcas (Deecke, 1998;Filatova et al, 2010;Ford, 1991;Weib, Symonds, Spong, & Ladich, 2011). The predictability with which groups of orcas use certain sets of sounds with recognizable acoustic features has led many researchers to conclude that orcas within each group use a discrete library of 7-17 calls that is adopted by convention (Ford, 1991;Kremers, Lemasson, Almunia, & Wanker, 2012;Rendell & Whitehead, 2001;Strager, 1995).…”
Section: Orca Sound Matching: Imitation Of Familiar Vocalizations?mentioning
confidence: 99%
“…Recent studies suggest that orcas will match the calls of other orcas that they hear in vocal exchanges (P. J. O. Miller et al, 2004;Weib et al, 2011).…”
Section: Orca Sound Matching: Imitation Of Familiar Vocalizations?mentioning
confidence: 99%
“…In O. orca , behavioural and genetic studies have provided evidence that vocal dialects are transmitted via vocal learning rather than genetic inheritance (reviewed in Rendell & Whitehead, 2001; Janik, 2009). There is further evidence that vocal learning is not limited to vertical transmission from mother to offspring, but also takes place horizontally between matrilines with similar and different dialects (Deecke, Ford & Spong, 2000; Janik, 2009; Weiß et al ., 2010). The specialized hunting techniques of certain killer whale populations, such as the intentional stranding observed at Península Valdés, Argentina, and in the Crozet Islands (Table 2), have also been suggested to be transmitted via social learning from generation to generation (Hoelzel, 1991; Guinet & Bouvier, 1995), although experimental data on this are not yet available.…”
Section: Cultural Transmissionmentioning
confidence: 99%